FADOI survey on chronic kidney disease and anaemia in internal medicine departments of Italian hospitals - Pietro Bocchi; Andrea Montagnani; Michele Meschi; Fulvio Pomero; Paola Piccolo; Antonella Valerio; Gualberto Gussoni; Dario Manfellotto; Francesco Dentali; Chronic Kidney Disease and Anaemia in Internal Medicine (CKD-AIM) FADOI Study Group (Italian Journal of Medicine, 2023)
The presence of anaemia in patients with chronic kidney disease (CKD) is associated with decreased quality of life, along with increased morbidity, mortality, and hospitalization rates. This, in turn, affects healthcare costs and the utilization of medical resources. The mechanisms involved in anaemia of CKD are diverse and complex. They include reduced production of endogenous erythropoietin (EPO), absolute and/or functional iron deficiency (due to inflammation leading to elevated levels of hepcidin), the diminished response of the bone marrow to EPO due to uraemic toxins, the shortened lifespan of red blood cells (RBC), and deficiencies in vitamin B12 or folic acid. [...]